Allopregnanolone Effects on Transmission in the Brain Stem Solitary Tract Nucleus (NTS). (21st May 2018) - Kim, Sojin; Kim, Sung-Moon; Oh, Bermseok; Tak, Jihoon; Yang, Eunhee; Jin, Young-Ho
Highlights: Allopregnanolone (ALLO) effects on visceral afferent synaptic transmission were tested in female rat hindbrain slices. Micromolar concentrations of ALLO increased frequency and decay time of spontaneous inhibitory postsynaptic currents. Submicromolar concentrations of ALLO induced extrasynaptic GABAergic inhibitory tonic current. ALLO suppressed solitary tract stimulation-evoked excitatory postsynaptic current amplitude in the low nanomolar range. ALLO administration increased failure of solitary tract stimulation to trigger action potentials in most neurons. Abstract: During pregnancy, the progesterone metabolite, allopregnanolone (ALLO), becomes elevated and has been associated with altered levels within the CNS and resulting changes in GABAA receptor function. Pregnant animals poorly compensate reflexes for a decrease in blood pressure during hemorrhage. Previous works suggested that ALLO decreases baroreflex responses by central actions, however, the underlying mechanisms are poorly understood. In this study, we tested ALLO actions on visceral afferent synaptic transmission at second-order neurons within medial portions of the nucleus tractus solitarius (NTS) using hindbrain slices from non-pregnant female rats. Solitary tract (ST) stimulation-evoked excitatory postsynaptic currents (ST-eEPSCs) in NTS neurons directly connected to vagal afferents within the ST. ST-eEPSCs were functionally identified as monosynaptic by the latency characteristics (low jitter = standard deviation of latency, ≤200 μs) to ST stimulation. Such second-order neurons all displayed spontaneous inhibitory postsynaptic currents (sIPSCs), and low micromolar concentrations of ALLO increased frequency and decay time. At submicromolar concentrations, ALLO induced a tonic, GABAergic inhibitory current and suppressed ST-eEPSCs' amplitude. While GABAA receptor antagonist, bicuculline, blocked all ALLO effects, gabazine only blocked sIPSC actions. In current-clamp mode, ALLO perfusion increased failure of ST stimulation to trigger action potentials in most neurons. Thus, our results indicate that ALLO acts to suppress visceral afferent ST synaptic transmission at first synapses by activating pharmacologically distinct GABAA subtypes at different concentration ranges. This ALLO-mediated attenuated visceral afferent signal integration in NTS may underlie reflex changes in blood pressure during gestation.